2015
DOI: 10.1177/0255761415607081
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing creativity in the music classroom

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 60 publications
(62 reference statements)
0
28
0
3
Order By: Relevance
“…Data were collected through questionnaires and a follow-up interview. All 26 participants were asked to complete a questionnaire consisting of 17 open-ended questions (see Appendix A), which was modified and developed from the one used with British teachers (see, for example, Howell, 2008;Bolden et al, 2010;Kokotsaki, 2011;Newton, L. & Beverton, 2012;and Kokotsaki & Newton, 2015). Any particular issues with the use of this Following the questionnaire, 10 teachers further participated in an interview to provide richer data on teachers' conceptions of creativity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were collected through questionnaires and a follow-up interview. All 26 participants were asked to complete a questionnaire consisting of 17 open-ended questions (see Appendix A), which was modified and developed from the one used with British teachers (see, for example, Howell, 2008;Bolden et al, 2010;Kokotsaki, 2011;Newton, L. & Beverton, 2012;and Kokotsaki & Newton, 2015). Any particular issues with the use of this Following the questionnaire, 10 teachers further participated in an interview to provide richer data on teachers' conceptions of creativity.…”
Section: Methodsmentioning
confidence: 99%
“…It is crucial to realise the important role of cultural and social environment on valuing and developing creativity (Amabile, 1982(Amabile, ,1983(Amabile, ,1996Simonton, 1984Simonton, ,1992Simonton, ,1994Csikszentmihalyi, 1996;Amabile & Conti, 1997;Niu & Sternberg, 2003;Newton, D., 2012b;Gauntlett & Thomsen, 2013;Kokotsaki & Newton, 2015). Cultural variation may result in different desirable behaviours in different contexts (Newton, D., & Newton, L, 2009;Newton, D. & Donkin, 2011;Kokotsaki & Newton, 2015).…”
Section: Challenging Environmental Context For Creativity In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Survey results indicated that while these teachers valued creativity, and thought they were assessing it, they were actually assessing musical knowledge. Kokotsaki and Newton () asked 17 pre‐service secondary music teachers in the UK to holistically assess the creativity of nine student‐produced musical compositions. The music compositions were rated as highly creative when they were appropriate to the task, and used a range of musical elements and devices, while imagination, originality, and variety were identified to a lesser extent as significant criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Newton () found that teachers identified answers that were ‘correct’ as creative. Kokotsaki and Newton () found that teachers rated student products as creative when they were appropriate to the task, while imagination, originality, and variety featured to a lesser extent as significant criteria. These studies demonstrate a strong bias in favour of convergence over divergence in teachers’ creativity assessments.…”
Section: Discussionmentioning
confidence: 99%